Relationship between synovial fluid ARGS‐aggrecan fragments, cytokines, MMPs, and TIMPs following acute ACL injury: A cross‐sectional study. Issue 12 (17th July 2015) - Tourville, Timothy W.; Poynter, Matthew E.; DeSarno, Michael J.; Struglics, André; Beynnon, Bruce D.
ABSTRACT: Severe knee trauma, such as an ACL disruption, produces aggrecan degradation as evidenced by elevated synovial fluid (SF) N‐terminal (393) Alanine–Arginine–Glycine–Serine (ARGS) neoepitope (or ARGS‐aggrecan) and is associated with inflammatory activity soon after injury. However, it is not known if this process persists for a substantial time interval following the initial trauma. The purpose of this study was to evaluate relationships between SF ARGS concentrations and an array of cytokines, matrix metalloproteases (MMPs), and tissue inhibitor of metalloproteases (TIMPs) during the initial 6 months following ACL rupture. SF samples from 67 ACL‐injured subjects (29 women) were analyzed within 6 months of injury (18–155 days), immediately prior to surgical ACL reconstruction. Relationships between ARGS and individual analyte concentrations, as well as MMP/TIMP ratios were evaluated. Statistically significant relationships were found between ARGS and basic fibroblast growth factor (FGF2) ( p = 0.03) and TIMP‐3 ( p = 0.01). Our findings suggest that FGF2, considered to be primarily catabolic in articular cartilage, is not downregulated as ARGS concentration declines over time since injury. In addition, these results support the hypothesis that an upregulation of TIMP‐3, the primary aggrecanase inhibitor, is elicited in response to increased aggrecan degradation, which may inhibit further cleavage. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1796–1803, 2015.